Calculating Price Elasticity of Demand

How to calculate price elasticity of demand.

price-elasticity-demand-formula

Price elasticity of demand = % change in Q.D. / % change in Price

  • To calculate a percentage, we divide the change in quantity by initial quantity. If price rises from $50 to $70. We divide 20/50 = 0.4 = 40%

Example of calculating PED

When the price of CD increased from $20 to $22, the quantity of CDs demanded decreased from 100 to 87.

What is the price elasticity of demand for CDs?

Calculating a Percentage

  • The price increases from $20 to $22. Therefore % change = 2/20 = 0.1 (10%)
    0.1 = 10% (0.1 *100)
  • Quantity fell by 13/100 = – 0.13 (13%)
  • Therefore PED = 13/-10
  • Therefore PED = -1.3

In this case demand is price elastic.

  • Therefore Demand is elastic. Elastic demand occurs when % change in quantity is greater than % change in price; when PED >1

Example 2

ped-elasticityi

  • Price rises from $15 to $30 (100% rise in price)
  • Quantity falls from 100 to 80 (20% fall)
  • PED – -20/100 = -0.2

Example 3

price-elastic-demand

In this case the PED

% change in QD = -50/100 = 0.5 = -50%

% change in price =10/50 = 0.2 = 20%

Therefore PED  = -2.5

Example 4

inelastic-demand

PED = -10/40 = -0.25

 

Advanced – difference between point and arc elasticity of demand

  1. Point elasticity of demand takes the elasticity of demand at a particular point on a curve. (using
  2. Arc elasticity measures elasticity at the mid point between the two selected points:

See also:

By on January 14th, 2017

10 thoughts on “Calculating Price Elasticity of Demand

    1. Economists consider both explicit and implicit costs while culculating profit while accountants do not, they only consider explicit cost.

  1. u should explain unit elasticity sith mathematical calculation and graphical as well. and rest of the elasticity =œ and elasticity =0.thanks.

  2. Please explain why you are not dividing by the average quantity demanded or the average price. In the first example you are dividing by the original quantity and the original price. My text book states the correct equations is
    (change)Qd /Qdaverage /(change)P/ P average –(which states the change in quantity demanded over the average of the old and new quantity demanded then that is divided by the change in price over the average of the old and new price

Leave a Reply

Your email address will not be published. Required fields are marked *